Una finestra sulla psichiatria tedesca. «Se venissimo ignorati completamente e se tutti agissero come se fossimo cose non esistenti...». Su un libro recente del neurobiologo Joachim Bauer - Annelore Homberg (Il sogno della farfalla, 2012)
The article is a comment on the recent and stimulating book Schmerzgrenze (The threshold of pain) by the German neurobiologist Joachim Bauer, which has not been translated into Italian thus far, in which Bauer rejects the concept of an innately demonic aggressive drive in man and shows, with the help of recent neurobiological discoveries, how the primary motivations of Homo sapiens are, on the other hand, characterized by a tendency towards social aggregation (social brain).